2013
DOI: 10.1093/mnras/stt259
|View full text |Cite
|
Sign up to set email alerts
|

The abundance of (not just) dark matter haloes

Abstract: We study the effect of baryons on the abundance of structures and substructures in a cold dark matter (CDM) cosmology, using a pair of high-resolution cosmological simulations from the Galaxies-Intergalactic Medium Interaction Calculation project. Both simulations use identical initial conditions, but while one contains only dark matter, the other also includes baryons. We find that gas pressure, reionization, supernova feedback, stripping and truncated accretion systematically reduce the total mass and the ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
187
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(214 citation statements)
references
References 88 publications
23
187
4
Order By: Relevance
“…White 2001;Sawala et al 2013). In the above, to make comparison with the Sheth-Tormen formulae, we have used FOF haloes.…”
Section: Halo Mass Functionsmentioning
confidence: 99%
“…White 2001;Sawala et al 2013). In the above, to make comparison with the Sheth-Tormen formulae, we have used FOF haloes.…”
Section: Halo Mass Functionsmentioning
confidence: 99%
“…Teyssier et al 2013); to the "too big to fail problem", which raises questions about the matching between dark matter halos and their stellar masses (e.g. Boylan-Kolchin et al 2011, Sawala et al 2013; to the nature of dark matter (e.g. Governato et al 2015); and to the identification of the sources that were able to reionize the universe (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This result is not shared by other hydrodynamic simulations. For example, Sawala et al (2013) found from the hydrodynamical simulation GIMIC (Crain et al 2009) that baryons reduce the mass of subhaloes less massive than 10 12 M , and the relative subhalo masses varies monotonically between 0.65 and 1 for subhaloes of mass 10 9 M and 10 14 M respectively. Additionally, the subhalo abundance is suppressed in GIMIC at small halo masses but never exceeds the N -body run for large halo masses.…”
Section: Introductionmentioning
confidence: 99%